Performance Measurement of CBIR Systems Based on different Techniques and Global Features (International Journal of Communication Systems and Network Technologies, 2016)
Because of the enormous increase in graphic information, there is a need of an efficient retrieval of images arises in this information era. Content based image retrieval (CBIR) is a method that searches similar images from a large database against a query image submitted by user. Indexing, retrieving, browsing, these are the fundamental steps involved in any image retrieval system. In Content based image retrieval system (CBIR), first features are extracted from available images in the database and later stored in the feature descriptor then same features are extracted from the input query image. Images which are similar they are retrieved. This paper presents a survey on various CBIR systems and different techniques and features which are used in these contents based image retrieval systems.
Keywords: CBIR; Precision; Recall; Feature Descriptor; Color; Texture